Experiências agroecológicas de comercialização no Rio Grande do Sul: Associação dos Agricultores Ecologistas de Ipê e Antonio Prado (AECIA) e Centro de Apoio ao Pequeno Agricultor (CAPA) - Nascimento, Fábio Schwab do (Universidade Federal de São Carlos, 2012)
This dissertation has as an objective to present the results of the research conducted for the Master Course of Agroecology and Rural Development of the Federal University of São Carlos. This study aimed to analyze the different existing processes of commercialization in the Rio Grande Do Sul in relation to the concept of organization of its producers and the forms of commercialization used. To develop the present work, a case study will be used, having as object two experiences in the Rio Grande Do Sul. The chosen experiences was the Association Ecologists Farmers Ipê and Antonio Prado (Ipê and Antonio Prado/RS) and the Center of Support Small Farmers (Santa Cruz do Sul/RS). It was conducted a socioeconomic analysis of these experiences, observing how its forms of organization and commercialization influences in the reached results.
Keywords: Agroecologia; Comercialização; Agricultura familiar; Agroecology; Commercialization; Family Farming; CIENCIAS AGRARIAS